IL-36β Promotes CD8+ T Cell Activation and Antitumor Immune Responses by Activating mTORC1 - Zhao, Xin; Chen, Xiaojuan; Shen, Xinghua; Tang, Peijun; Chen, Chen; Zhu, Qitai; Li, Muyao; Xia, Rui; Yang, Xi; Feng, Chao; Zhu, Xinguo; Zhu, Yibei; et al. (Frontiers in Immunology, 2019)
Cytokine-amplified functional CD8+ T cells ensure effective eradication of tumors. Interleukin 36α (IL-36α), IL-36β, and IL-36γ share the same receptor complex, composed of the IL-36 receptor (IL-36R) and IL-1RAcP. Recently, we revealed that IL-36γ greatly promoted CD8+ T cell activation, contributing to antitumor immune responses. However, the underlying mechanism of IL-36-mediated CD8+ T cell activation remains understood. In the current study, we proved that IL-36β had the same effect on CD8+ T cell as IL-36γ, and uncovered that IL-36β significantly activated mammalian target of rapamycin complex 1 (mTORC1) of CD8+ T cells. When mTORC1 was inhibited by rapamycin, IL-36β-stimulated CD8+ T cell activation and expansion was drastically downregulated. Further, we elucidated that IL-36β-mediated mTORC1 activation was dependent on the pathway of phosphatidylinositol 3 kinase (PI3K)/Akt, IκB kinase (IKK) and myeloid differentiation factor 88 (MyD88). Inhibition of PI3K or IKK by inhibitor, or deficiency of MyD88 respectively suppressed mTORC1 signal, causing arrest of CD8+ T cell activation. Additionally, it was validated that IL-36β significantly promoted mTORC1 activation and antitumor function of CD8+ tumor-infiltrating lymphocytes (TILs) in vivo, resulting in inhibition of tumor growth and prolongation of survival of tumor-bearing mice. Taken together, we substantiated that IL-36β could promote CD8+ T cell activation through activating mTORC1 dependent on PI3K/Akt, IKK and MyD88 pathways, leading to enhancement of antitumor immune responses, which laid the foundations for applying IL-36β into tumor immunotherapy.